Deposition process for preparing super-hard super-wear-resistant 1N14 color coating from multi-element nitride
Through PVD technology and Ti-Zr-Cr-N composite material, a high hardness, high wear resistance 1N14 color coating is achieved, solving the problem of high cost and short life of precious metal coatings, and providing a decorative effect similar to real gold and performance, and cost reduction.
Patent Information
- Application Number
- CN202411091024.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-09
- Publication Date
- 2025-01-14
AI Technical Summary
In the prior art, the precious metal real gold coating is costly and has a short decorative life. It is difficult for non-precious metal nitride coatings to achieve similar appearance decorative effects as real gold. The color difference is large and cannot meet the needs of watches, jewelry and electronic products. 1N14 color decoration requirements.
Through PVD technology, Ti-Zr-Cr-N composite coating is adopted, and ion plating technology, high-power pulse magnetron sputtering technology or arc technology are used to adjust the titanium-zirconium ratio, combine gradient air intake to relieve stress, and achieve 1N14 color Deposition of coating.
A decorative effect is obtained that is highly similar to that of the real gold coating. The coating hardness and wear resistance are greatly improved, the cost is reduced, the color difference is close to that of the real gold, and the wear resistance is greater than that of the real gold coating.
Smart Images

Figure CN119307857A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of decorative surface treatment of watches, jewelry and electronic products, and in particular to a deposition process for preparing super-hard and super-wear-resistant 1N14 color coatings using multi-component nitrides. Background Art
[0002] PVD technology is a process that uses physical processes to achieve material transfer, transferring atoms or molecules from a source to the surface of a substrate. Through this technology, certain particles with special properties (such as high strength, wear resistance, heat dissipation, corrosion resistance, etc.) can be sprayed on a matrix with lower performance, thereby making the matrix have better performance.
[0003] 1N14 color is the color standard of gold commonly used in the watch industry, and PVD technology is a conventional surface decorative treatment technology for preparing 1N14 color coatings. However, conventional precious metal real gold (including its alloys) coatings, in addition to being extremely expensive, have soft coating textures, are difficult to maintain their real gold color for a long time during use, have a short decorative life, and have almost no protective properties. Using non-precious metal nitride coatings, such as titanium nitride or zirconium nitride and other multi-component nitride coatings, it is difficult to obtain an appearance decorative effect that is very similar to real gold. Using l, a, and b as quantitative constants, the color difference values of the titanium nitride solution in the existing schemes are: l: ~78, a: ~2.5, b: ~35, the color difference values of the zirconium nitride solution are: l: ~81, a: ~-0.5, b: ~30, and the color difference values of the 1N14 real gold coating are: l: ~88, a: ~2.1, b: ~21.5. That is, the color difference values of the non-precious metal nitride coatings in the prior art have large deviations, which are far from meeting the actual use requirements of 1N14 color for decorative surface treatment of watches, jewelry and electronic products. Summary of the invention
[0004] The purpose of the present invention is to overcome the shortcomings of the above-mentioned background technology. Through PVD surface treatment technology, a multi-nitride preparation super-hard and super-wear-resistant 1N14 color coating deposition process is provided. Non-precious metal compound coating is used to achieve a 1N14 color decorative effect that is highly similar to precious metal real gold coating, and the hardness and wear resistance of the obtained coating are far superior to precious metal real gold coating.
[0005] The coating of the present invention is mainly deposited by ion plating technology (high-power pulsed magnetron sputtering technology or arc technology), and its main feature is the composite of multiple materials (titanium, zirconium, chromium), wherein the chromium content is less than 10%, and the titanium content and the zirconium content are both in the range of 10%-80%. By adjusting different titanium-zirconium ratios, a 1N14 color coating can be obtained. In terms of the process, gradient air intake is used to relieve stress and ensure film-substrate adhesion performance. In this solution, the air pressure and target power remain consistent during the deposition process, and the process flow is relatively stable.
[0006] To achieve the purpose of the present invention, the deposition process of the multi-component nitride for preparing the super-hard and super-wear-resistant 1N14 color coating comprises the following steps:
[0007] (1) The sample substrate is cleaned in liquid form in an automated cleaning line;
[0008] (2) Place the sample substrate in a coating machine and pre-evacuate it;
[0009] (3) Pre-vacuum and perform glow cleaning in the coating machine;
[0010] (4) After glow cleaning, film deposition is performed in a coating machine;
[0011] (5) Cooling and removal from the furnace after film deposition;
[0012] The film deposition includes adhesion layer deposition, transition layer deposition and final coating deposition. The film deposition parameters are as follows: time is 105-115 min, gas is argon and nitrogen, duty cycle is 45-55%, volume flow rate of argon is 400-1000 sccm, volume flow rate of nitrogen is 100-200 sccm, bias voltage is 145-155 V;
[0013] The coating is a Ti-Zr-Cr-N composite material coating.
[0014] Furthermore, in some embodiments of the present invention, the atomic ratio of Ti, Zr and Cr metals in the Ti-Zr-Cr-N composite material coating is 4.3-7.4:3.8-4.2:0.9-1.1, preferably 5-7:4:1.
[0015] Furthermore, in some embodiments of the present invention, the sample substrate includes but is not limited to metal, ceramic and polymer products.
[0016] Furthermore, in some embodiments of the present invention, the operating procedure of step (1) is: placing the sample in a cleaning basket, placing it in a fully automatic cleaning line, and sequentially performing degreasing, dewaxing, spraying, rinsing, slow pulling, and baking processes.
[0017] Furthermore, in some embodiments of the present invention, the operation flow of step (2) is: the operator confirms that the turntable rotates normally, confirms that the conductivity of the turntable is normal, hangs the sample in a suitable position on the turntable, rotates the turntable to confirm that the sample is hung in a suitable position, and rotates without scratches.
[0018] Furthermore, in some embodiments of the present invention, the operation flow of step (3) is: enter the coating system, inject 1000 sccm of argon, start the bias power supply, set the bias to 1000 V, the duty cycle to 50%, and the duration to 10 minutes.
[0019] Furthermore, in some embodiments of the present invention, the operating procedure of the adhesion layer deposition in step (4) is as follows: enter the coating system, inject 400 sccm of argon gas, start the bias power supply, set the bias voltage to 150 V, the duty cycle to 50%, and turn on the chromium target after the furnace environment is stable, the target current is 30 A, the deposition time is 10 min, and the adhesion layer deposition is completed.
[0020] Furthermore, in some embodiments of the present invention, the operating process of the transition layer deposition in step (4) is as follows: fill with 100 sccm of nitrogen, start the titanium target and zirconium target power supplies, the peak current is 800A, the power is 5-7KW and 4KW, the chromium target is kept on, the current is maintained at 30A, the bias voltage is maintained at 150V, the duty cycle is 50%, the coating time is 30min, and the transition layer deposition is completed.
[0021] Furthermore, in some embodiments of the present invention, the operating procedure of the final coating deposition in step (4) is as follows: turn off the chromium target, keep the parameters of the titanium target and the zirconium target unchanged compared with the transition layer deposition, increase the nitrogen flow rate to 200 sccm, maintain the bias voltage at 150 V, the duty cycle at 50%, and the coating time at 60 min to complete the deposition.
[0022] Furthermore, in some embodiments of the present invention, the operation process of step (5) is: turn off all target power supplies, turn off the gas, turn off the bias, cool to room temperature under vacuum, and take the sample out of the furnace.
[0023] Compared with the prior art, the advantages of the present invention are as follows:
[0024] (1) The coating material obtained by the 1N14 color coating deposition process of the present invention has a decorative effect highly similar to 1N14 color as a whole. By controlling the proportions of different metals, a 1N14 color decorative effect coating can be obtained, while obtaining ultra-hard and ultra-wear-resistant coating protection performance.
[0025] (2) The color difference value of the standard 1N14 color real gold coating is: l: ~88, a: ~2.1, b: ~21.5, and the hardness of the real gold 1N14 color coating is: ~4GPa, while the color difference value of the non-precious metal compound coating 1N14 color coating obtained by the present invention is: l: ~82, a: ~2.4, b: ~22.2, and the coating hardness is: ~30GPa.
[0026] (3) For high-end surface treatment products that require real gold coatings, the present invention provides an alternative non-precious metal compound coating process with highly similar decorative performance, ultra-long service life, excellent protection performance and greatly reduced cost. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1It is a schematic diagram of the film structure obtained by the process of the present invention;
[0028] Figure 2 The wear resistance test result of the real gold coating is carried out according to the method of the present invention;
[0029] Figure 3 The wear resistance test is carried out according to the method described in the present invention, and the wear resistance test results of the coating obtained by the process of Example 1 of the present invention are shown. DETAILED DESCRIPTION
[0030] In order to make the purpose, technical scheme and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. Additional aspects and advantages of the present invention will be partially given in the following description, partially become apparent from the following description, or be understood through the practice of the present invention. It should be understood that the following description is only used to explain the present invention and is not intended to limit the present invention.
[0031] As used herein, the terms "comprises," "including," "having," "containing," or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a composition, process, method, article, or apparatus that comprises the listed elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, process, method, article, or apparatus.
[0032] When amount, concentration or other value or parameter is expressed as range, preferred range or a series of upper preferred value and lower preferred value limit range, this should be understood as specifically disclosing all ranges formed by any pairing of any range upper limit or preferred value and any range lower limit or preferred value, regardless of whether the range is disclosed separately. For example, when disclosing range "1 to 5", described range should be interpreted as including range "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5" etc. When numerical range is described in this article, unless otherwise stated, the range is intended to include its end value and all integers and fractions within the range.
[0033] Singular forms include plural references unless the context clearly indicates otherwise. "Optional" or "either" means that the subsequently described event or incident may or may not occur, and that the description includes instances where the event occurs and instances where it does not.
[0034] The indefinite articles "a" and "an" before the elements or components of the present invention have no limitation on the quantity requirements (i.e. the number of occurrences) of the elements or components. Therefore, "a" or "an" should be interpreted as including one or at least one, and the elements or components in the singular form also include the plural form, unless the quantity obviously refers to the singular form only.
[0035] In addition, the descriptions of the terms "one embodiment", "some embodiments", "examples", "specific examples", or "some examples" described below mean that the specific features, structures, materials, or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic expressions of the above terms do not necessarily refer to the same embodiment or example. Moreover, the technical features involved in the various embodiments of the present invention can be combined with each other as long as they do not conflict with each other.
[0036] The present invention mainly measures two aspects of performance, and the performance test standards / methods are as follows:
[0037] 1. Color performance
[0038] The color difference of real gold 1N14 color is used as the standard, and the a value and b value within ±0.5 are considered qualified.
[0039] 2. Wear resistance
[0040] Use special steel wool (steel wool model: #0000, manufacturer: Bon Star STEEL WOOL, steel wool needs to be stored dry), apply a load of 500gf, the test head area is 2*2cm, rub back and forth on the sample surface at a speed of 40cycle / min and a stroke of about 40mm; after 500 cycles, observe whether there are friction marks on the sample surface.
[0041] Example 1
[0042] A process for preparing super-hard and super-wear-resistant 1N14 color coating from multi-component nitrides (titanium, zirconium, chromium), comprising the following steps:
[0043] Step 1: The sample substrate (substrate is metal---stainless steel) is automatically cleaned by liquid cleaning line
[0044] Step 2: Place the sample substrate in the coating machine for pre-vacuuming;
[0045] Step 3: Glow cleaning in the coating machine;
[0046] Step 4: Depositing the film layer in the coating machine;
[0047] Step 5: Cool and remove from the oven;
[0048] The PVD coating is a Ti-Zr-Cr-N (metal atomic ratio 5:4:1) composite material coating.
[0049] The operation process of step one is: put the sample into a cleaning basket, place it in a fully automatic cleaning line, and perform degreasing, dewaxing, spraying, rinsing, slow pulling, and baking processes in sequence.
[0050] The operation process of step 2 is as follows: the operator wears a hat, gloves and a mask, and wears an anti-static suit, confirms that the rotating rack rotates normally, confirms that the conductivity of the rotating rack is normal, hangs the sample in a suitable position on the rotating rack, rotates the rotating rack to confirm that the sample is hung in a suitable position, and rotates without scratches.
[0051] The operation flow of step three is as follows: close valves 1 and 2, enter the coating system, flush argon gas at 1000 sccm, start the bias power supply, set the bias voltage to 1000 V, the duty cycle to 50%, and the duration to 10 minutes, and perform plasma cleaning.
[0052] The operation flow of step 4 is as follows: enter the coating system, flush with 400sccm of argon, start the bias power supply, set the bias voltage to 150V, the duty cycle to 50%, and turn on the chromium target after the furnace environment is stable. The target current is 30A, the deposition time is 10min, and the adhesion layer is completed. Fill with 100sccm of nitrogen, start the titanium target and zirconium target power supplies, the peak current is 800A, and the power is 5KW and 4KW. The chromium target remains on and the current is maintained at 30A. The bias voltage is maintained at 150V, the duty cycle is 50%, and the coating time is 30min to complete the transition layer. Turn off the chromium target, the parameters of the titanium target and the zirconium target remain unchanged, and the nitrogen flow rate is increased to 200sccm. The bias voltage is maintained at 150V, the duty cycle is 50%, and the coating time is 60min to complete the deposition.
[0053] The operation flow of step five is: turn off all target power supplies, turn off the gas, turn off the bias, cool to room temperature under vacuum, and take the sample out of the furnace.
[0054] Color difference of the obtained products: 82.2, 2.03, 21.5
[0055] Abrasion test showed no scratches.
[0056] Example 2
[0057] Compared with Example 1, the metal atomic ratio of Ti-Zr-Cr-N is increased to 7:4:1. The specific adjustment is step 4, and the other steps remain unchanged.
[0058] The operating procedure of step four is: enter the coating system, flush with 400sccm of argon, start the bias power supply, set the bias to 150V, the duty cycle to 50%, and turn on the chromium target after the furnace environment is stable. The target current is 30A, the deposition time is 10min, and the adhesion layer is completed. Fill in 100sccm of nitrogen, start the titanium target and zirconium target power supplies, the peak current is 800A, the power is 7KW and 4KW. The chromium target remains on and the current is maintained at 30A. The bias is maintained at 150V, the duty cycle is 50%, and the coating time is 30min to complete the transition layer. Turn off the chromium target, the parameters of the titanium target and the zirconium target remain unchanged, and the nitrogen flow rate is increased to 200sccm. The bias is maintained at 150V, the duty cycle is 50%, and the coating time is 60min to complete the deposition.
[0059] The color difference of the obtained products is: 81.61, 2.16, 21.08, and the color is qualified.
[0060] Abrasion test showed no scratches.
[0061] Comparative Example 1
[0062] Compared with Example 1, the metal atomic ratio of Ti-Zr-Cr-N is increased to 9:4:1, and the specific adjustment is step 4, while the other steps remain unchanged.
[0063] The operating procedure of step four is: enter the coating system, flush with 400sccm of argon, start the bias power supply, set the bias to 150V, the duty cycle to 50%, and turn on the chromium target after the furnace environment is stable. The target current is 30A, the deposition time is 10min, and the adhesion layer is completed. Fill in 100sccm of nitrogen, start the titanium target and zirconium target power supplies, the peak current is 800A, the power is 9KW and 4KW. The chromium target remains on and the current is maintained at 30A. The bias is maintained at 150V, the duty cycle is 50%, and the coating time is 30min to complete the transition layer. Turn off the chromium target, the parameters of the titanium target and the zirconium target remain unchanged, and the nitrogen flow rate is increased to 200sccm. The bias is maintained at 150V, the duty cycle is 50%, and the coating time is 60min to complete the deposition.
[0064] The color difference of the obtained products is: 81.72, 2.24, 19.8, and the color is unqualified.
[0065] Comparative Example 2
[0066] Compared with Example 1, the Ti-Zr-Cr-N metal atomic ratio is reduced to 3:4:1, and the specific adjustment is step 4, and the other steps remain unchanged.
[0067] The operating procedure of step four is: enter the coating system, flush with 400sccm of argon, start the bias power supply, set the bias to 150V, the duty cycle to 50%, and turn on the chromium target after the furnace environment is stable. The target current is 30A, the deposition time is 10min, and the adhesion layer is completed. Fill in 100sccm of nitrogen, start the titanium target and zirconium target power supplies, the peak current is 800A, and the power is 3KW and 4KW. The chromium target remains on and the current is maintained at 30A. The bias is maintained at 150V, the duty cycle is 50%, and the coating time is 30min to complete the transition layer. Turn off the chromium target, the parameters of the titanium target and the zirconium target remain unchanged, and the nitrogen flow rate is increased to 200sccm. The bias is maintained at 150V, the duty cycle is 50%, and the coating time is 60min to complete the deposition.
[0068] The color difference of the obtained products is: 82.64, 1.66, 22.52, and the color is unqualified.
[0069] Comparative Example 3
[0070] Compared with Example 1, the nitrogen content of the reaction gas is increased while maintaining the Ti-Zr-Cr-N metal atomic ratio of 5:4:1. The specific adjustment is step 4, and the other steps remain unchanged.
[0071] The operating procedure of step four is: enter the coating system, flush with 400sccm of argon, start the bias power supply, set the bias to 150V, the duty cycle to 50%, and turn on the chromium target after the furnace environment is stable. The target current is 30A, the deposition time is 10min, and the adhesion layer is completed. Fill in 100sccm of nitrogen, start the titanium target and zirconium target power supplies, the peak current is 800A, and the power is 5KW and 4KW. The chromium target remains on and the current is maintained at 30A. The bias is maintained at 150V, the duty cycle is 50%, and the coating time is 30min to complete the transition layer. Turn off the chromium target, the parameters of the titanium target and the zirconium target remain unchanged, and the nitrogen flow rate is increased to 220sccm. The bias is maintained at 150V, the duty cycle is 50%, and the coating time is 60min to complete the deposition.
[0072] The color difference of the obtained products is: 81.38, 2.82, 24.6, and the color is unqualified.
[0073] Comparative Example 4
[0074] Compared with Example 1, the nitrogen content of the reaction gas is reduced while maintaining the Ti-Zr-Cr-N metal atomic ratio of 5:4:1. The specific adjustment is step 4, and the other steps remain unchanged.
[0075] The operating procedure of step four is: enter the coating system, flush with 400sccm of argon, start the bias power supply, set the bias to 150V, the duty cycle to 50%, and turn on the chromium target after the furnace environment is stable. The target current is 30A, the deposition time is 10min, and the adhesion layer is completed. Fill in 100sccm of nitrogen, start the titanium target and zirconium target power supplies, the peak current is 800A, and the power is 5KW and 4KW. The chromium target remains on and the current is maintained at 30A. The bias is maintained at 150V, the duty cycle is 50%, and the coating time is 30min to complete the transition layer. Turn off the chromium target, the parameters of the titanium target and the zirconium target remain unchanged, and the nitrogen flow rate is increased to 180sccm. The bias is maintained at 150V, the duty cycle is 50%, and the coating time is 60min to complete the deposition.
[0076] The color difference of the obtained products is: 81.91, 1.79, 18.87, and the color is unqualified.
[0077] It will be easily understood by those skilled in the art that the above description is merely an example of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A deposition process for preparing super-hard and super-wear-resistant 1N14 color coating from multi-component nitrides, characterized in that: The process comprises the following steps: (1) The sample substrate is cleaned in liquid form in an automated cleaning line; (2) Place the sample substrate in a coating machine and pre-evacuate it; (3) Pre-vacuum and perform glow cleaning in the coating machine; (4) After glow cleaning, film deposition is performed in a coating machine; (5) Cooling and removing from the furnace after film deposition; Wherein, the film layer deposition includes adhesion layer deposition, transition layer deposition and final coating deposition; the coating is a Ti-Zr-Cr-N composite material coating.
2. The deposition process for preparing super-hard and super-wear-resistant 1N14 color coating from multi-component nitrides according to claim 1 is characterized in that: The film deposition parameters are as follows: time is 105-115 min, gases are argon and nitrogen, duty cycle is 45-55%, volume flow rate of argon is 400-1000 sccm, volume flow rate of nitrogen is 100-200 sccm, bias voltage is 145-155V.
3. The deposition process for preparing super-hard and super-wear-resistant 1N14 color coating from multi-component nitrides according to claim 1 is characterized in that: The atomic ratio of Ti, Zr and Cr metals in the Ti-Zr-Cr-N composite material coating is 4.3-7.4:3.8-4.2:0.9-1.1; preferably, the atomic ratio of Ti, Zr and Cr metals in the Ti-Zr-Cr-N composite material coating is 5-7:4:
1.
4. The deposition process for preparing super-hard and super-wear-resistant 1N14 color coating from multi-component nitrides according to claim 1 is characterized in that: The sample substrate is a metal, ceramic or polymer product.
5. The deposition process for preparing super-hard and super-wear-resistant 1N14 color coating from multi-component nitrides according to claim 1 is characterized in that: The operation process of step (1) is as follows: put the sample into a cleaning basket, place it in a fully automatic cleaning line, and perform degreasing, dewaxing, spraying, rinsing, slow pulling, and baking processes in sequence.
6. The deposition process for preparing super-hard and super-wear-resistant 1N14 color coating from multi-component nitrides according to claim 1 is characterized in that: The operation flow of step (2) is as follows: the operator confirms that the rotating rack rotates normally, confirms that the conductivity of the rotating rack is normal, hangs the sample on the appropriate position of the rotating rack, rotates the rotating rack to confirm that the sample is hung in a proper position, and rotates without scratching.
7. The deposition process for preparing super-hard and super-wear-resistant 1N14 color coating from multi-component nitrides according to claim 1 is characterized in that: The operation flow of step (3) is as follows: enter the coating system, inject argon gas at 1000 sccm, start the bias power supply, set the bias voltage to 1000 V, the duty cycle to 50%, and the duration to 10 minutes.
8. The deposition process for preparing super-hard and super-wear-resistant 1N14 color coating from multi-component nitrides according to claim 1 is characterized in that: The operation flow of the adhesion layer deposition in step (4) is as follows: enter the coating system, inject 400 sccm of argon gas, start the bias power supply, set the bias voltage to 150V, the duty cycle to 50%, and after the furnace environment is stable, turn on the chromium target, the target current is 30A, the deposition time is 10 minutes, and the adhesion layer deposition is completed.
9. The deposition process for preparing super-hard and super-wear-resistant 1N14 color coating from multi-component nitrides according to claim 1, characterized in that: The operation flow of transition layer deposition in step (4) is as follows: fill with nitrogen at 100 sccm, start the power supply of titanium target and zirconium target, the peak current is 800A, the power is 5-7KW and 4KW, the chromium target is kept on, the current is maintained at 30A, the bias voltage is maintained at 150V, the duty cycle is 50%, the coating time is 30min, and the transition layer deposition is completed; preferably, the operation flow of the final coating deposition in step (4) is as follows: turn off the chromium target, the parameters of the titanium target and the zirconium target remain unchanged compared with the transition layer deposition, the nitrogen flow rate is increased to 200 sccm, the bias voltage is maintained at 150V, the duty cycle is 50%, the coating time is 60min, and the deposition is completed.
10. The deposition process for preparing super-hard and super-wear-resistant 1N14 color coating from multi-component nitrides according to claim 1, characterized in that: The operation flow of step (5) is: turn off all target power supplies, turn off the gas, turn off the bias, cool to room temperature under vacuum, and take the sample out of the furnace.